Weather effects on returns: An empirical study of UK stock market - Zhao, Juan (2011)
This study investigates the weather effects on UK stock market. Three weather variables of London are examined: sunshine hours, temperature and humidity level. FTSE100 index is chosen as the proxy of UK stock market. The period of the sample data is covered from January 1996 to December 2005. Both the weather effects on returns and volatility are studied with several methodologies. Empirical results show that extreme sunshine and temperature conditions and their interaction conditions have impacts on stock returns and volatility. This provides an evidence to support for behavioral finance against efficient market hypothesis (EMH) in that not all investors all fully rational and stock price may have other determinants other than its fundamental value.